The role of fragmented habitat in the conservation of bat faunas: their implications in ecosystem conservation and management - Mohd Sah, Shahrul Anuar (Universiti Sains Malaysia, 2016)
Malaysia is one of the major global hotspots for bat diversity with 118 species recorded, which is around 5% of all bat species in the world. While some species in the region are adapted to open areas and edge itats the vast majority of Malaysian bats are dependent on forest. Bats perform several essential ecological functions in tropical forests. Fruit bats are important pollinators and seed dispersal agents, that maintain forest ecosystems and allow forest regeneration.